The given system of equations is:
-3x - 2y = -12 ---(1)
9x + 6y = -9 ---(2)
To solve this system, we can use the method of substitution.
From equation (1), we can rearrange it to solve for x:
-3x = -12 + 2y
Dividing all terms by -3:
x = (2y - 12)/-3
x = (12 - 2y)/3
Now, substitute the value of x in equation (2):
9((12 - 2y)/3) + 6y = -9
Multiplying through by 3 to clear the fraction:
9(12 - 2y) + 18y = -27
Expand and simplify:
108 - 18y + 18y = -27
The y terms cancel out, and we're left with:
108 = -27
This is a contradiction, which means the system of equations has no solution.
What is the solution in the following system? {-3×-2y=-12; 9×+6y=-9
1 answer